Comparative efficacy of two Ivermectin Pour-on anthelmintics in beef steers in a commercial feedyard - A.J. Tarpoff; T. Guichon; Daniel U. Thomson; Benjamin W. Wileman; Christopher D. Reinhardt (Kansas Agricultural Experiment Station Research Reports, 2012)
Generic products generally have a cost advantage for beef producers over brand-name products. Recently, many beef producers have debated whether to utilize generic anthelmintics in cow/calf herds and feeder cattle. If generics are to be justified, the products must be proven to have efficacy similar to the brand-name product. Previous studies have indicated that generic macrocyclic lactones are less effective in controlling gastrointestinal parasites of cattle than the original brand-name products. The objective of this study was to compare the efficacy of Vetrimec (Norbrook Laboratories Limited, Newry, Co. Down, Northern Ireland) pour-on and Ivomec (Merial Animal Health, Duluth, GA) pour-on by utilizing the fecal egg reduction test in newly arrived feedlot steers.
Keywords: Cattlemen& #x27; s Day; 2012; Kansas Agricultural Experiment Station contribution; no. 12-231-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1065; Beef Cattle Research; 2012 is known as Cattlemen& #x27; s Day; Beef; Ivermectin Pour-on; Feedlot; Anthelmintics